Factors affecting new product development success: A study on manufacturing sector in Malaysia - Mohd Azrul, Abdul Aziz (2015)
New product development has become significantly important for the manufacturing industries. It’s the important factors to drive the success or failure of a company where growth and development of the company are solely depend on its ability to introduce the new product. Therefore, the new product development is the criteria that cannot be questioned by the company in maintaining a competitive advantages. The modern business environment nowadays are focused on the development and integration of the supply chain. Supply chain has become an important topic which emphasis on variables that might affect the company and the new product development. This study aims to determine the relationship between some of the supply chain variables that might affect the growth of new product development for the manufacturing industries. There are many important factors in the supply chain where it has contributed to the new product development success. For this study, the factors that been identified are the communication, logistics, supply chain strategy, product development strategy and the top management supports. A total of 238 respondents in various companies within the manufacturing industry in Malaysia’s manufacturing sectors has participated in this study by completing the questionnaire survey. SPSS was use to analyze the data and hypothesis testing using several statistical analysis such as reliability analysis, correlation and regression analysis. From this analysis, the supply chain variables showed a significant relationship to the successful new product development in the view of Malaysian manufacturing sectors. It is hope that this study will be beneficial the others in understanding the key terms and can be implement into the new product development so that it is become more successful